Oxilipinas no estudo da biodiversidade de microalgas de água doce - Moreira, Ingritt Caroline (Universidade Federal de São Carlos, 2018)
This research focuses on the oxylipins with eighteen carbons, compound derived of polyunsaturated fatty acids, produced by twenty-two species of freshwater algae, one cyanobacteria and three species of plants, with emphasis on green microalgae from the Chlorophyta and Charophyta phylum, and also species of the Selenastraceae family (Chlorophyta, Chlorophyceae, Sphaeropleales). The aim was detected, identified and quantified oxylipins derived from linoleic and linolenic acids produced by microorganisms using High-Performance Liquid Chromatography coupled tandem Mass Spectrometry technique. It was used microalgae from the Culture Collection of Freshwater Microalgae (CCMA-UFSCar), species already classified by classic and / or molecular taxonomy, as well as the species of plants for comparative purposes. For the experiments, the material came from the end of stationary phase. Once the compounds were identified by these techniques, it was tested the possibility of using profiles as diacritical characteristics in a chemotaxonomic approach for formation of hierarchical clusters. The pharmacological potential of these compounds was discussed since they present antibiotic and anti-inflammatory activities. Other possible commercial applications were approached since microalgae revealed their potential value as natural sources of hydroxy fatty acids. No oxylipin was exclusively observed to determinated organism that could represents as species indicator. This condition limits the use of oxylipins derived from C18 PUFAs in the taxonomy of the Selenastraceae family, but even so, these compounds provide complementary information for organisms that may be useful in their identification. There was universality regarding the presence of oxylipins analysed in all the taxonomic groups studied. The strains belonging to Chlorophyta division showed the highest total concentrations of oxylipins. Charophyta algae have a concentration of oxylipins dozens of times lower than Chlorophyta, and similar to concentrations found in plants, which may be related to the evolutionary proximity among plants and Charophyta.
Oxylipins in the study of the biodiversity of freshwater microalgae
Keywords: Oxilipinas; Chlorophyta; Charophyta; Selenastraceae; Hidroxi-ácidos; Oxo-ácidos; Oxylipins; Chlorophyta; Charophyta; Selenastraceae; Hydroxy-acids; Oxo-acids; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOQUIMICA DOS MICROORGANISMOS; CIENCIAS BIOLOGICAS::BOTANICA::BOTANICA APLICADA; CIENCIAS BIOLOGICAS::BOTANICA::TAXONOMIA VEGETAL; CIENCIAS BIOLOGICAS::BOTANICA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA